Truncation of C-Terminal Intrinsically Disordered Region of Mycobacterial Rv1915 Facilitates Production of “Difficult-to-Purify” Recombinant Drug Target - Antil, Monika; Gouin, Sébastien G.; Gupta, Vibha (Frontiers in Bioengineering and Biotechnology, 2020)
Availability of purified drug target is a prerequisite for its structural and functional characterization. However, aggregation of recombinant protein as inclusion bodies (IBs) is a common problem during the large scale production of overexpressed protein in heterologous host. Such proteins can be recovered from IB pool using some mild solubilizing agents such as low concentration of denaturants or detergents, alcohols and osmolytes. Though misfolding may not be the sole factor behind protein aggregation, intrinsically disordered protein regions (IDPRs) may also lead to non-specific agglomeration because of unstructured loops and coils. This study reports optimization of solubilization buffer for recovery of soluble and biologically active recombinant mycobacterial Rv1915/ICL2a from IBs. Even though the solubilization of target protein could be obtained with mild agents (sarcosine and βME) without the use of denaturants, purification could not be achieved. Bioinformatics analysis revealed the C-terminal of Rv1915/ICL2a to be an IDPR which probably promoted protein aggregation and reduced binding to Ni-NTA affinity matrix. With this rationale, 90 residues from the C-terminal of Rv1915/ICL2 were truncated, the variant successfully purified and characterized for ICL and MICL activities, supporting the disordered nature of Rv1915/ICL2a C-terminal. When a region that has definite structure associated in some mycobaterial strains such as CDC 1551 and disorder in others for instance Mycobacterium tuberculosis H37Rv, it stands to reason that larger interface in the later may have implication in binding to other cellular partner.